Approaches in Teaching Children with Reading Problems - I Dewa Putu Raka Rasana (Universitas Pendidikan Ganesha, 2012)
English has been taught in elementary school. In learning English, the English teacher teaches the four skills, namely, reading, writing, speaking, and listening. The reading process is one of the activities that needs to be given a great attention. There are some important approaches that can be used in the reading process, namely, individualized reading, language experience, shared reading, and so forth. The English teacher should be familiar with the important approaches of the reading process as well as the materials that reflect each approach. When the teacher reads about these approaches, he thinks about what he wrote about how he reads in the elementary school. He also needs to think where his experience fits and how he will teach reading.